Activities of daily living and quality of life during treatment with neoadjuvant chemoradiotherapy and after surgery in patients with esophageal cancer. Issue 6 (20th October 2016) - Haj Mohammad, Nadia; De Rooij, Sophia; Hulshof, Maarten; Ruurda, Jelle; Wijnhoven, Bas; Erdkamp, Frans; Sosef, Meindert; Gisbertz, Suzanne; van Berge Henegouwen, Mark; Sprangers, Mirjam; van Laarhoven, Hanneke
Abstract : Background and Objectives: Neoadjuvant chemoradiation (nCRT) followed by esophagectomy is a treatment with curative intent for resectable esophageal cancer. The aim of this study was to measure activities of daily living (ADL) and quality of life (QoL), and to examine correlates of changes in ADL and QoL. Methods: A prospective study was performed with three time points (baseline, 1 week after the end of nCRT, 3‐months post‐surgery) together with a cross‐sectional post‐treatment study. ADL was measured with the Amsterdam Linear Disability Score (ALDS), and QoL with the EORTC QLQ‐C30 and the OES‐18. Regression analysis was performed to identify factors associated with changes in ADL and QoL. Results: Seventy‐six patients were included in the prospective study, 79 in the cross‐sectional study. After nCRT, ALDS decreased from 90 to 88 ( P < 0.01) and remained stable after surgery. Global QoL decreased from 75 to 61 ( P < 0.01); no significant changes were observed after surgery. Only timing of the measurement of ALDS was negatively associated with non‐maximum ALDS (n = 155, based on both studies) and QoL (n = 76) ( P < 0.01). Conclusions: Patients who undergo nCRT plus surgery should be prepared to experience a short‐term decline in ADL and QoL. The findings of this study can support patients and healthcare workers to guide expectations. J. Surg. Oncol. 2016;114:684–690 . © 2016 Wiley Periodicals, Inc.